A Case of Pyloric Diverticulum - H. A. Tangkilisan; S. M. Salendu-Warouw (Paediatrica Indonesiana, 1992)
EG, an 11-year-old- Indonesian boy, 30 kg of body weight and 130 em of body length was admitted to the Department of Child Health, Gunung Wenang General Hospital Manado with pyloric diverticulum. The main complaint was sudden frequent hematemesis. The first attack of this symptom developed when he was 9 years old. Physical examination showed only tenderness in the epigastric region. The laboratory findings were normal. The diagnosis was based on the Barium meal X-ray, which showed an additional appearance in the pyloric region (prebulbar). He was treated with conservative treatment and after 10 days of hospitalization, he was discharged in good condition.